Merchant gang governance and earnings management - Chun Liu; Liang Sun; Yuhang Xu (China Journal of Accounting Studies (CJAS), 2024)
This study integrates the multilateral punishment mechanism theory with the characteristics of Chinese society-"acquaintance," "face," and "relationship"-to analyze and test the governance mechanism of merchant gangs on earnings management for the first time. Findings reveal that (1) merchant gangs significantly reduce earnings management in Chinese listed companies, holding after various robustness checks; (2) companies more influenced by merchant gang governance face harsher multilateral punishments upon exposure of financial misconduct, with more complete conditions strengthening this effect; (3) merchant gangs have a stronger governance impact on firms with native management, and formal institutions enhance their governance role. This research provides empirical evidence for the multilateral punishment mechanism theory and contributes to understanding merchant gang governance in China.
Keywords: 650; earnings management; formal institutions; Merchant gang governance; multilateral punishment mechanism